Terapan Aksiologi pada Artificial Intelligence Chatbot : Study pada Respon ChatGpt - Ig Jarot Febri Setyo Wibowo; Agung Winarno (Switch : Jurnal Sains dan Teknologi Informasi, 2025)
The rapid advancement of technology has made artificial intelligence (AI), particularly generative chatbots, an integral part of everyday life. These chatbots, powered by Natural Language Processing (NLP) and deep learning technologies, are widely used in various fields such as customer service, education, and entertainment. However, the increasing prevalence of such technologies brings forth important philosophical concerns, particularly in the realm of axiology—the branch of philosophy that deals with the nature of values, including the practical and ethical implications of knowledge and technology. This study investigates the practical benefits and ethical responsibilities associated with generative chatbots, using ChatGPT as a case study. The research examines whether ChatGPT adheres to the axiological principles of science, specifically its usefulness in enhancing human life and its ethical responsibilities. Through a qualitative content analysis, this research evaluates the responses of ChatGPT to a series of questions based on the axiological framework outlined by Sumantri. The study focuses on two main aspects of science's axiological evaluation: the practical benefits of science and technology, and the ethical responsibilities tied to their application. The findings indicate that ChatGPT is capable of providing useful insights that contribute to human understanding, improve quality of life, simplify complex tasks, and offer solutions to various problems. However, the ethical considerations of AI technology, such as fairness, transparency, and accountability, remain a crucial area of concern. This research highlights the importance of balancing technological progress with ethical responsibility, emphasizing that AI systems like ChatGPT must be developed and applied in ways that align with human values to ensure their positive impact on society.